Fabrikasi Kabel Tunggal NYA Diameter 2 mm, Bahan Tembaga, Kapasitas 120 m/Jam - Muhammad Rafli Hakim Azizi; Syamsul Hadi; Rizky Dwi Alvian Saputra; M. Dawam El Hakim; Tegar Prayoga (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
The short circuit is a single electrical cable made of copper, also known as a non-standard NYA type type electrical cable, which endangers safety as a problem faced in the field. The fabrication objective is to obtain a single NYA cable with a diameter of 2 mm, from copper material that meets standards, SNI 04-2698-1999 or SNI 04-6629.3-2006. Fabrication methods include: design and manufacture of single cable molds (die) diameters 7, 6, 5, 4, 3, 2 mm; selection includes purchasing pure Copper cable materials in accordance with standards; gradual reduction in diameter from 8 mm to 2 mm; preparing extrusion machines with PVC type plastic material for single cable insulation; manufacture of standard single NYA cables with a diameter of 2 mm using a simultaneous extrusion machine by running a copper wire with a diameter of 2 mm followed by winding the cable every 50 m; and quality-dimensional-packaging inspection. The fabrication results are in the form of a standard NYA type single cable, SNI 04-2698-1999 or SNI 04-6629.3-2006 with a diameter of 2 mm with a total production cost of IDR 5,500/m, and a production duration of 0.5 minutes/m, which means that the NYA type cable can be used for a maximum power flow of 4,400 W.